PENGARUH MODEL PEMBELAJARAN CONTEXUAL TEACHING LEARANING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PKN KELAS IV SEKOLAH DASAR - Lay, Abir Yohindro; Naitili, Cornelia Amanda; Nahak, Roswita Lioba (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2024)
PKn learning is expected to be a vehicle for students to learn about themselves and the surrounding environment as well as prospects for further development in applying it in daily life. However, there are still many students who lack mastery of the material and obtain scores that have not reached the KKTP. This happens because the learning model used is usually a conventional learning model. In addition, it also identifies problems, namely First, the learning outcomes of PKN students have not reached KKTP, second, teachers tend to use conventional learning models where teachers teach more oriented to lecture methods so that learning is more teacher-centered. Third, the teacher's lack of attention to the student's ability to receive the material because it is chasing time so that the material is completed quickly. The purpose of this study is to determine the influence of the continuous teaching learning model on the learning outcomes of PKn in grade IV students of Oepura 4 Multi-level SDI, Kupang City. This type of research is a quantitative research classified as Quasi Experimental research, using a pretest posttest control group design. The sampling technique uses a saturated sampling technique with a sample of 30 respondents. The instruments used in this study are tests and documentation. The data was analyzed using data normality tests, homogination tests, linearity tests, and hypothesis tests. The results showed that the average posttest score of the experimental class and the control class posttest using the t-test was 78.33 > 1.50 with a difference of 15.82. Furthermore, through hypothesis testing (Independent Samples Tests) it was shown that the value of sig. (2-tailed) t-test for Equality of Means of 0.000<0.05 means that H0 is rejected and Ha is accepted. The conclusion of this study is the application of the significant influence of the contexual teaching learning model on the learning outcomes of PKn students in grade IV of SD Inpres Berstrata Oepura 4, Kupang City.